The issuance of sentence in audience - Cristoval De la Cruz, Timoteo (2020)
In this work, the author will expose about the lack or scarce issuance of sentences in the audience; call it a single hearing, trial process and audience of the case in second instance. This situation has turned the exceptionality of deferring the judgement in a rule. Thus, the cases resolved through final decisions issued during the months of January to August 2019 in the Superior Court of Justice of Junín will be analyzed; specifically, in the cases of the province of Huancayo.